2012
DOI: 10.1021/jf300510m
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Aminoethyl Cysteine Ketimine Decarboxylated Dimer in Mice: Effect on Plasma Antioxidant Potential

Abstract: Aminoethylcysteine ketimine decarboxylated dimer (AECK-DD) is a natural compound with antioxidant properties of a new family of sulfur-containing amino acids. It has been detected in human urine and plasma, in mammalian cerebellum, and in dietary vegetables. In this study, we first demonstrate the absorption of AECK-DD in mice from AECK-DD-supplemented diet, using both liquid chromatography with electrochemical detection and gas chromatography coupled with mass spectrometry. AECK-DD circulates in the plasma of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…As discussed by Piazzon et al, AECK-DD has been reported to be present at micromoles per liter concentrations in normal human plasma, normal human urine and bovine cerebellum . Here, we wish to compare these published results with our previous findings.…”
supporting
confidence: 50%
See 4 more Smart Citations
“…As discussed by Piazzon et al, AECK-DD has been reported to be present at micromoles per liter concentrations in normal human plasma, normal human urine and bovine cerebellum . Here, we wish to compare these published results with our previous findings.…”
supporting
confidence: 50%
“…Interestingly, Piazzon et al were able to detect this compound in the plasma of mice fed 0.05% AECK-DD in the diet for 24 h. The concentration of dehydro-AECK-DD was not specified, but from a comparison of the intensity of the AECK-DD peak to that of the dehydro-AECK-DD peak in the GC-SIM-MS chromatographic profile shown by the authors (Figure 3 in ref ), we estimate that the concentration of dehydro-AECKK-DD in the plasma was about 10% that of AECK-DD. The authors also reported a significant increase in the plasma antioxidant activity in the mice fed AECK-DD in the diet compared to that observed in the plasma of mice fed standard laboratory chow . The authors conclude in the last sentence of their abstract that “These results demonstrate for the first time the absorption of AECK-DD from [the] diet and the physiological relevance of this compound through its antioxidant action in vivo.” However, we have several reservations concerning the physiological relevance of the results reported by Piazzon et al…”
mentioning
confidence: 73%
See 3 more Smart Citations